2022
DOI: 10.1186/s12913-022-08663-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a general practitioner-to-general physician eConsult service (eConsultant) in Australia

Abstract: Background In response to lengthy wait times for specialist outpatient appointments, electronic consultation (eConsult) services have developed globally, providing asynchronous, secure and timely communication between general practitioner (GP) and specialist. This study aims to track adoption of a Queensland eConsultant service in two Australian Primary Health Networks (Western Queensland and Brisbane South) to understand key barriers and enablers to adoption and inform modification of the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…4,19 eConsults can help circumvent provider shortages in these settings. 20,21 Comments from the PCPs we interviewed reinforced our chart review findings. PCPs affirmed their appreciation for eConsults and their intent to act on eConsult specialists' recommendations, but noted that their patients' inability to access or afford some types of treatment impacted whether they would incorporate the recommendation into their treatment plan.…”
Section: Discussionmentioning
confidence: 58%
“…4,19 eConsults can help circumvent provider shortages in these settings. 20,21 Comments from the PCPs we interviewed reinforced our chart review findings. PCPs affirmed their appreciation for eConsults and their intent to act on eConsult specialists' recommendations, but noted that their patients' inability to access or afford some types of treatment impacted whether they would incorporate the recommendation into their treatment plan.…”
Section: Discussionmentioning
confidence: 58%
“…Our literature review and expert interviews aimed to identify and synthesize currently postulated adoption barriers and improvement strategies for digital health adoption more broadly and validate their relevance in general practice settings. We initially retrieved 1276 records in the literature search, of which we included 24 articles 13 , 15 , 17 19 , 22 , 23 , 28 44 .…”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified technological, social, and organizational adoption barriers. More than 90% of included studies reported organizational adoption barriers 13 , 15 , 17 , 18 , 22 , 23 , 28 44 (23/24), with more than half reporting high workload 17 , 22 , 29 , 30 , 34 , 36 44 and a lack of time 13 , 15 , 17 , 18 , 23 , 28 , 29 , 31 34 , 36 , 40 , 42 (each 14/24; 58%) as predominant barriers. Another 88% of studies identified social adoption barriers 13 , 15 , 17 , 18 , 22 , 23 , 28 32 , 35 44 (21/24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our eConsultant service was piloted and implemented with a general (internal) medicine physician specialist, able to provide advice across all medical subspecialities bar dermatology. 14 The specialist was employed by an urban tertiary hospital which provided hospital-based general medicine clinics. In 2019, the hospital complemented this with an eConsultant service to two Australian regions (Western Queensland, and Brisbane South), resulting in 87% of requests for advice to the eConsultant replacing a traditional outpatient referral.…”
Section: Introductionmentioning
confidence: 99%